The feasibility of converting ex-coal mining void into aquaculture in North Kalimantan - Yoppie Christian; Andy Afandi; Budi Prabowo; Novit Rikardi; Desmiwati Desmiwati (Brawijaya University, 2023)
Ex-coal mining void has changed landscape shape, physical-chemical, and soil biological properties. As a form of post-mining management, the company must restore damaged land and increase its benefits for the surrounding community, one of which is as a freshwater aquaculture area. This study was conducted in a 50.26 ha void in the concession area of the coal mining company PT. Mitrabara Adiperdana (MAP) in Malinau Regency, North Kalimantan. The method used is by examining the physical quality of the environment in the laboratory using the quality standards in Indonesian Government Regulation (PP) No. 82 of 2001 and No. 22 of 2021. A study was also conducted on the assessment of community acceptance. The study found that freshwater aquaculture for pangasius (Pangasius sp.), snakehead (Channa striata), and tilapia (Oreochromis sp.) is appropriate to apply on location with several notes: reducing the concentration of suspended solids; reducing the content of phosphate and ammonia, and reducing the concentration of lead (Pb). Regarding these issues, two methods can be used: technology of turbine and nanobubble and natural-based solution through wetland ecosystem and void basin rehabilitation. At the same time, education and promotion of the surrounding community can be applied by involving communities during the piloting and demonstration plot process.